IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN DI KABUPATEN KUANTAN SINGINGI: (Studi Kasus Akta Kematian) - Khapiz Al-Farisi; Hasim As’ari (Public Service and Governance Journal, 2023)
Every citizen has the right to civil registration in the sense that he has the right to request an authentic deed from a state official. It is still rare for residents to realize how important a deed is for them in sustaining their life. The purpose of this study is to analyze and describe the implementation of the policy for implementing population administration in the possession of death certificates for the community at the Population and Civil Registration Office of Kuantan Singingi Regency and to identify obstacles in implementing the policy for implementing population administration in making death certificates at the Population and Civil Registration Service for Kuantan Regency Singingi. Qualitative research as a research method that starts from assumptions, interpretive/theoretical lenses, and studies of research problems that look at how individuals or groups interpret social or humanitarian problems. The results of the research that the researchers conducted regarding the implementation of population administration administration policies in Kuantan Singingi Regency (a case study of death certificates), namely, the policy of implementing population administration regarding death certificates had not been properly implemented by the Kuantan Singingi Regency Population and Civil Registration Service, this was obtained from several factors, namely Policy standards and targets/measures and objectives, resources, characteristics of implementing agents, implementor communication, attitude and position of executors, social, economic and political environment. The second obstacle is the lack of socialization related to population administration. The third obstacle is the lack of public awareness.